A rare case of aortic sinuses of valsalva fistula to multiple cardiac chambers secondary to periannular aortic abscess formation from underlying Brucella endocarditis - Sabzi, Feridoun; Heidari, Aghighe; Faraji, Reza (German Medical Science GMS Publishing House, 2015)
The concomitant presence of abnormal connection from three aortic valsalva sinuses to cardiac chambers is a rare complication of native aortic endocarditis. This case report presents a 37-year-old Iranian female patient who had native aortic valve endocarditis complicated by periannular abscess formation and subsequent perforation to multi-cardiac chambers associated with congestive heart failure and left bundle branch block. Multiple aorto-cavitary fistulas to right atrium, main pulmonary artery, and formation of a pocket over left atrial roof were detected by transthoracic echocardiogram (TTE). She had received a full course of antibiotics therapy in a local hospital and was referred to our center for further surgery. TTE not only detected multiple aorto-cavitary fistulas but also revealed large vegetation in aortic and mitral valve leaflets and also small vegetation in the entrance of fistula to right atrium. However, the tricuspid valve was not involved in infective endocarditis. She underwent open cardiac surgery with double valve replacement with biologic valves and reconstruction of left sinus of valsalva fistula to supra left atrial pocket by pericardial patch repair. The two other fistulas to main pulmonary artery and right atrium were closed via related chambers. The post-operative course was complicated by renal failure and prolonged dependency to ventilator that was managed accordingly with peritoneal dialysis and tracheostomy. The patient was discharged on the 25 day after admission in relatively good condition. The TTE follow-up one year after discharge revealed mild paravalvular leakage in aortic valve position, but the function of mitral valve was normal and no residual fistulas were detected.